2022
DOI: 10.1159/000526942
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Proteins as Dental Caries Biomarkers: A Systematic Review

Abstract: Salivary proteins play an important role in repairing mechanisms of damaged tissues and the maintenance of oral health. However, there is a dearth of information in the literature regarding the concentrations of salivary proteins in caries-free (CF) and caries-active (CA) subjects. Hence, this systematic review was conducted to update our previous systematic review published in 2013 that aimed to assess the association between caries and salivary proteins by comparing CF and CA individuals. Thereby, evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…Regarding RC presence at 12 months, both groups showed signi cant differences in salivary protein concentration assessed at 6 months. The ndings are consistent with previous studies that have shown that salivary protein variation in patients is associated with increased risk of caries [46,47] . However, there are few studies that have emphasised the differences in salivary composition between individuals with and without RC.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding RC presence at 12 months, both groups showed signi cant differences in salivary protein concentration assessed at 6 months. The ndings are consistent with previous studies that have shown that salivary protein variation in patients is associated with increased risk of caries [46,47] . However, there are few studies that have emphasised the differences in salivary composition between individuals with and without RC.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, alterations in the concentration of several molecules presented in saliva have proven valuable in diagnosing and monitoring oral diseases, including dental caries, periodontitis, oral squamous cell carcinoma, and Sjo ¨gren's syndrome. 46,47 The interaction between saliva and polymeric materials used in oral rehabilitation or tissue regeneration is inherent, which may lead to chemical-physical-biological changes in polymeric materials, such as hydrophilicity, degradation, morphology, surface properties, and biocompatibility. 48,49 The acidic conditions can lead to phase/morphology change and even degradation of polymeric materials that are sensitive to pH.…”
Section: Highly Movable and Wet Environmentmentioning
confidence: 99%
“…Notably, alterations in the concentration of several molecules presented in saliva have proven valuable in diagnosing and monitoring oral diseases, including dental caries, periodontitis, oral squamous cell carcinoma, and Sjögren's syndrome. 46,47…”
Section: Oral Environmentmentioning
confidence: 99%
“…Lately, scientists are studying the potential of saliva as an alternative, noninvasive biofluid for the diagnosis of several pathological conditions by the evaluation of biomarkers and monitoring the therapeutic outcomes. , Being the first fluid facing exogenous substances, the composition and quality of saliva play a major role in caries development. It is considered an essential host factor in the colonization of bacteria and progression of caries. , Various antimicrobial salivary proteins and enzymes play a prominent role in maintaining the overall oral health . By the establishment of a range for the normal values of salivary and exogenous components, the oral health status of an individual can be monitored.…”
Section: Introductionmentioning
confidence: 99%
“…3,14 Various antimicrobial salivary proteins and enzymes play a prominent role in maintaining the overall oral health. 15 By the establishment of a range for the normal values of salivary and exogenous components, the oral health status of an individual can be monitored. Among the several other specific enzymes and electrolytes, salivary α-amylase is the most abundant enzyme found in human saliva.…”
Section: Introductionmentioning
confidence: 99%